Relationship Between Three Risk Factor Of DM-Pulmonary TB Incident At RSI Siti Aisyah Madiun in 2023 - Lauretha, Armydika; Marsanti, Avicena Sakufa; Abidin, Zaenal (Health Science UDINUS, 2023)
Diabetes mellitus is an infectious disease that has three times the risk of developing pulmonary tuberculosis. The purpose of this study was to analyze the relationship between age, body mass index status, and history of TB exposure and the incidence of DM-TB at Siti Aisyah Madiun Islamic Hospital. This research method uses analytic observational research with a case-control. The total respondents in the case group were 32 patients, and the control group had 32 patients for the 2021–2023 period. The research instrument used was a questionnaire and an observation paper. The results of this study were based on age (adj.RR = 5.082, 95% CI: 1.282–20.145, p 0.021), status factor Body Mass Index (BMI) (adj.RR = 0.172, 95% CI: 0.051–0.573, p 0.004), and TB Exposure (p 0,439). The conclusion of this study is that age and BMI status variables have a relationship. So therefore, DM patients should maintain their diet and adopt a healthy lifestyle.